Pixar storytelling : rules for effective storytelling based on Pixar's greatest films - Movshovitz, Dean (2015)
"Pixar Storytelling is about effective storytelling rules based on Pixar's greatest films. The book consists of ten chapters, each of which explores an aspect of storytelling that Pixar excels at. Learn what Pixar's core story ideas all have in common, how they create compelling, moving conflict and what makes their films' resolutions so emotionally satisfying. The book also examines Pixar's character development, unique, intricate story structure and use of theme, all of which are key to the studio's storytelling achievements."--Amazon